Agrargeographische Folgen der Urbanisierung von Amman/Jordanien - Barham, Nasim; Mensching, Horst G. (ERDKUNDE, 1987)
Jordan is at present suffering from an increasing shortage in its domestic food supply. For example, the production of wheat as a staple food crop contributes only 16% to the country’s required supply (1985). The loss of arable land on the highland plateaux has therefore to be taken particularly seriously. Among other reasons, this is caused by the rapid urbanization of Irbid with its university and the growth of the capital city Amman. Vast areas in the north of Jordan are being encroached upon especially in the limited high land region suitable for intensive agriculture between the Jordan rift valley and the desert hinterland. During the 1920’s the urban development area of Amman amounted to no more than 3 sq km, while by 1936 it had increased to 8 sq km and had extended to over 20 sq km by 1940.At the end of the 1950s the urban development area totalled 84 sq km. This trend has continued over the past two decades. Today Greater Amman encompasses more than 380 sq km. This equals 9% of the area permanently used for rainfed cultivation, as outlying parts of the expanding capital lie in the cultivated highlands. In addition, the increasing environmental pollution as well as the steadily rising demand for water in Amman and its suburbs (e.g. Zarqa), are operating at the expense of intensive agriculture in this predominantly arid land.